A randomised controlled trial among cleaners-Effects on strength, balance and kinesiophobia - Holtermann Andreas; Sjøgaard Gisela; Ektor-Andersen John; Jørgensen Marie; Søgaard Karen (BMC, 2011)
Abstract Background Cleaners constitute a job group with poor health and low socioeconomic resources. Therefore, there is a great need for scientifically documented health promoting initiatives for cleaners. However, both workplace initiatives and high quality intervention studies are lacking. The aim of this study was to evaluate the effects of a 3-month workplace trial with interventions to improve physical or cognitive behavioural resources among cleaners. Methods A cluster randomised controlled trial was conducted among 294 female cleaners from 9 workplaces. The participants were allocated to three groups: Physical coordination training (PCT, n = 95), Cognitive behavioural theory-based training (CBTr, n = 99) and Reference group (REF, n = 100). Interventions were conducted during work hours for an average of 1 hour/week. Muscle strength was measured by maximal voluntary contractions in trunk/extension, and shoulder abduction/elevation. Postural balance was measured on a force platform. Kinesiophobia was measured with Tampa Scale for Kinesiophobia. Test and questionnaires were completed at baseline and at 3-month follow-up and analyses followed the intention-to-treat (ITT) principle with last observation carried forward in case of missing data at follow-up. Reports and analyses are given on true observations as well. Results ITT-analyses revealed that PCT improved strength of the trunk (p < .05) and postural balance (p < .05) compared to CBTr and REF. Based on true observations the strength and balance improvements corresponded to ~20% and ~16%, respectively. ITT-analyses showed that CBTr reduced kinesiophobia compared to PCT and REF (p < .05). Based on true observations, the improvement corresponded to a ~16% improvement. Conclusion This workplace-based intervention study including PCT and CBTr among cleaners improved strength and postural balance from PCT, and kinesiophobia from CBTr. The improved strength, postural balance and kinesiophobia may improve the cleaners' tolerance for high physical work demands. Future studies should investigate the potential in the combination of PCT and CBTr in a workplace intervention. Trial registration Current controlled trials ISRCTN96241850